El mito del manejo seguro de los plaguicidas en los países en desarrollo - García, Jaime E. (CATIE, Turrialba (Costa Rica), 2015)
n the the last two decades, in devcloping counlries. rnany training aClivitics for tbe safe use of peslicides llave taken place. However follow up evaluatioDS oC sorne oC ¡hese training eourses has revealed that even Ihough in most cases there has been a transfer oC knowledgc_ this has not res ultcd in a significant change of aU itude. lt seems ¡hat the training activi ties ha\'e become a process of informi ng of cxist ing dangers <I nd of Ihe safely standa rds that must be followed . \Ioith no real possibilities of changing Ihe daily habits of most workers that use these products. The word safe. \Ioidely and repeatedly used in the training eourses on pest icide managemcnt, is a mylh that offers Ihe participants a false sense of security, because Ihere is no practical impl ementation of safc management as such. The need to make greater efforts towards the disscmination of agricultural practices which reduce or eliminate the ll§C oC these products is emphasized